PARADOXICAL PERCEPTIONS ON SYRIANS’ FORCED MIGRATION TO TURKEY: A CASE STUDY OF ISTANBUL MUHTARS - (:unkn) unknown (My University, 2019)
As one of Syria’s neighbors, Turkey has become a refuge formore than 3.5 million forced Syrian migrants. Though many ofthem are living in Turkey’s border cities, in or around therefugee camps, many others have already dispersed to othercities. Among these cities, Istanbul has the largest Syriancommunity. Drawing on a qualitative field work in Istanbul’sneighborhoods, this study explores the Syrian migration toIstanbul and reports the attitudes towards this movement ofthe local neighborhood and village headmen, known as muhtarsin the Turkish local administrative system. As the study shows,their attitudes towards forced Syrian migrants are paradoxical,marked both by feelings of disturbance, worry and uneasiness,and at the same time welcome and support. The studyconcludes by discussing historical and cultural reasons forthese paradoxical attitudes by relating them to theunderstanding of hospitality in Turkish society to show how socio-psychological explanations of attitude formationtowards Syria’s forced migrants seem more appropriate.

Suriye’ye komşu ülkelerden biri olan Türkiye, yerinden edilmiş üç buçuk milyonu aşkın Suriyeli’ye sığınak oldu. Sınır kentlerinde bulunan mülteci kamplarında ve bu kampların çevresinde yoğun olarak yaşayan Suriyeliler İstanbul başta olmak üzere ülkenin pek çok büyük kentine de dağılmış haldeler. İstanbul’un mahallelerinde, Türkiye’nin bürokratik örgütlenmesi içinde yerel yönetim sisteminin en alt kademesinde bulunan mahalle yöneticisi muhtarlar nezdinde gerçekleştirilen bir saha çalışmasına dayanan bu makale, İstanbul’daki Suriyeli göçüne yakından bakarken söz konusu yerel yöneticilerin bu göç hareketi karşısındaki tutumlarını incelemektedir. Çalışma, muhtarların Suriyeli göçüne ilişkin tutumlarının çelişkili nitelikte olduğu ve özellikle, endişe, huzursuzluk, misafirperverlik ve destek gibi birbiriyle çelişkili sayılabilecek unsurlar çerçevesinde şekillendiğini ortaya koymaktadır. Söz konusu çelişkili tutumun tarihsel ve kültürel sebeplerini Türkiye toplumunun misafirperverlik anlayışıyla ilişkilendirerek tartışan çalışma, tutum oluşumuna yönelik yazında yer alan sosyo-psikolojik açıklamaların yerinden edilmiş Suriyelilere yönelik tutumları değerlendirmek için daha uygun olduğu sonucuna ulaşmıştır.
SURİYELİLER’İN TÜRKİYE’YE ZORUNLU GÖÇÜNE DAİR PARADOKSAL ALGILAR: İSTANBUL MUHTARLARI ÖRNEĞİ
Keywords: Uluslararası İlişkiler; Siyasi Bilimler